16.9k views
2 votes
Solve the system of equation using any method.

Y=4x-9
Y=x-3

User Blankface
by
4.5k points

2 Answers

2 votes

y=4x-9

y=x-3

-4x + y = -9

-x +y = -3 //-1

-4x + y = -9

x - y = 3

---------------------

-3x = -6

x = 2

y = 2-3

y = -1

User Naadira
by
5.1k points
4 votes

Answer:

(2, -1)

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination

Explanation:

Step 1: Define systems

y = 4x - 9

y = x - 3

Step 2: Solve for x

  1. Substitute in y: 4x - 9 = x - 3
  2. Subtract x on both sides: 3x - 9 = -3
  3. Add 9 to both sides: 3x = 6
  4. Divide 3 on both sides: x = 2

Step 3: Solve for y

  1. Define: y = x - 3
  2. Substitute in x: y = 2 - 3
  3. Subtract: y = -1
User Tae Soo Kim
by
4.5k points